PATTERN OF CERVICAL RADICULOPATHY AS DIAGNOSED BY ELECTRODIAGNOSTIC STUDIES: Cervical Radiculopathy - Khan, Omer Jamshed; Waheed, Akhtar; Ali, Liaqat (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To determine the pattern of cervical radiculopathy presenting to a military care set up using electro diagnostic techniques.Study Design: Descriptive cross sectional study.Place and Duration of Study: The study was conducted at the Armed Forces Institute of Rehabilitation Medicine Rawalpindi from July 2012 to December 2012.Subjects and Methods: Seventy three patients who were diagnosed as cases of cervical radiculopathy on electro diagnostic testing were included in the study. Demographics and frequency of involvement of different levels were noted.Results: Of the total 73 patients, 51 (69.9%) were males and 22 (30.1%) females, with a mean age of 48.01 ± 13.5 years. Left side predominated with 46.6% involvement whereas 39.7% of the patients had right sided radiculopathy and 13.7% had bilateral involvement. The most common radiculopathy encountered in this study was C7 which affected 25 (34.2%) patients, followed by C6 affecting 17 (23.3%) patients. Radicuolpathy affecting multiple upper segments like C5, C6 and C7 were a close third presenting in 15 (20.5%) patients. C8, T1 radiculopathy of the lower segments was diagnosed in 13 (17.8%) patients whereas the least common upper limb radiculopathy was C5, present in only 3 (4.1%) patients.Conclusion: Cervical radiculopathies affecting C7 and C6 roots were the most common ones encountered in our study, similar to international data. The cervical spine allows for greater movement and therefore is more prone to such developments. The reasons why C7 and C6 roots are most affected need to be studied further.